Computational study of shear strengthened of RC continuous beam using CFRP sheet with different wrapping scheme - Om Balkou, Mhimed Ramadan (2011)
Nowadays the using of carbon fiber reinforced polymer CFRP composites as an externally bonded reinforcement has become one of the alternatives solutions to repair shear defect on reinforced concrete structure. Therefore, this research intended to study and investigate the effectiveness of using externally bonded CFRP strips in strengthened RC continuous beams, as well as to study the behavior of RC continuous beams repair with CFRP strips for initially strengthened. A total of five RC continuous beams with size of 150x350x5800 mm was simulated and involves 0/90 degree orientation of CFRP strips in fully wrap schemes (4 sides and 3 sides). Five beams was analyzed by using ABAQUS software. The analysis results indicated that of externally bonded CFRP strips has enhanced the shear capacity of continuous RC beam. The numerical results also show good agreement with the experimental.